2018
DOI: 10.2147/jpr.s166934
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with posterosuperior labral tear: a comparison with patients with other shoulder disorders

Abstract: BackgroundAmong the various causes of shoulder pain, the glenoid labral tear is likely to be overlooked due to its ambiguous symptoms, especially if clinicians do not have a prior suspicion, making it difficult to diagnose, unlike adhesive capsulitis or a rotator cuff tear. Therefore, the aim of this study was to evaluate the clinical features of posterosuperior (PS) labral tear.MethodsOf the patients who visited the clinic, the medical records of patients with shoulder pain who underwent shoulder magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The authors performed arthroscopy in 18 patients by using MR arthrography as the reference standard and suggested that shoulder sonoarthrography is more accurate than conventional ultrasonography in the diagnosis of anterior labral tears. In a recent arthrography study, Park 16 evaluated the clinical characteristics of patients with posterior superior labral tears using MRI, conventional ultrasonography, and sonoarthrography. However, the authors did not evaluate the diagnostic accuracy of sonoarthrography in posterior labral tears.…”
Section: Discussionmentioning
confidence: 99%
“…The authors performed arthroscopy in 18 patients by using MR arthrography as the reference standard and suggested that shoulder sonoarthrography is more accurate than conventional ultrasonography in the diagnosis of anterior labral tears. In a recent arthrography study, Park 16 evaluated the clinical characteristics of patients with posterior superior labral tears using MRI, conventional ultrasonography, and sonoarthrography. However, the authors did not evaluate the diagnostic accuracy of sonoarthrography in posterior labral tears.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, SP has neuromusculoskeletal causes such as rotator cuff tear [3], rotator cuff tendinopathy [4], labral tear [5], bursitis [6] and long head of biceps tendinopathy [7].…”
Section: Introductionmentioning
confidence: 99%